The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fchem.2019.00240
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of AMB-FUBINACA Biotransformation Pathways in Human Liver Microsome and Zebrafish Systems by Liquid Chromatography-High Resolution Mass Spectrometry

Abstract: In this study, the metabolic profiles of a new illicit drug AMB-FUBINACA were investigated using both human liver microsome and zebrafish models. Liquid chromatography Q Extractive HF Hybrid Quadrupole-Orbitrap mass spectrometry (LC-QE-HF-MS) was employed to analyze the metabolic sites and pathways. AMB-FUBINACA was added to the in vitro liver microsome incubation model to simulate the metabolic processes in human body. The results showed that a total of 17 metabolites were generated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 22 publications
(21 reference statements)
2
26
0
Order By: Relevance
“…In a recent report where AMB‐FUBINACA was associated with a massive intoxication, the parent compound was not detected in blood while the carboxylic metabolite was detected at high concentrations in the urine samples. During the processing of this paper, Xu et al also reported the metabolic profiles of AMB‐FUBINACA using both human liver microsome and zebrafish models. Although in this work, a higher number of metabolites was found, in both cases the main metabolic pathways of the phase I metabolism included ester hydrolysis, hydroxylation, and a combination of both processes, while glucuronidation served as the main metabolic pathway of the phase II metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent report where AMB‐FUBINACA was associated with a massive intoxication, the parent compound was not detected in blood while the carboxylic metabolite was detected at high concentrations in the urine samples. During the processing of this paper, Xu et al also reported the metabolic profiles of AMB‐FUBINACA using both human liver microsome and zebrafish models. Although in this work, a higher number of metabolites was found, in both cases the main metabolic pathways of the phase I metabolism included ester hydrolysis, hydroxylation, and a combination of both processes, while glucuronidation served as the main metabolic pathway of the phase II metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…GC-MS and LC-MS are the methods most frequently used to detect and quantify ADB-FUBINACA and AMB-FUBINACA in biological and/or seized samples [2,3,39,40,[49][50][51], as presented in Tables 2 and 3, respectively. LC-MS is the preferred technique for the analytical determination of these thermally unstable compounds [52][53][54].…”
Section: Methods For Sc Detectionmentioning
confidence: 99%
“…The m/z 109, m/z 253 and m/z 338 fragments of ADB-FUBINACA were also previously observed in 2013 by Uchiyama et al [9] using the LC-QTOF/MS with a photodiode array (PDA) detector, and in 2014 by Takayama et al [38] using ultraperformance liquid chromatography with electrospray ionization-tandem mass spectrometry (UPLC/ESI-MS/MS). On the other hand, the analysis of the characteristic fragment ions of AMB-FUBINACA revealed that the amide bond was most susceptible to cleavage, thus forming a fragment ion at m/z 253.0772 (C 15 H 10 FN 2 O + ), and the cleavage between the indazole ring and fluorobenzyl produced the fluorobenzyl ion (C 7 H 6 F + ) at m/z 109.0448 [39]. Additional ions (m/z 145, 324, 383) were reported by Kevin et al [40], using gas chromatography coupled to mass spectrometry (GC-MS).…”
Section: Chemistry and Chemical Analysismentioning
confidence: 99%
“…Ester hydrolysis was also found to be one of the prevailing human metabolic pathways, whereas amide hydrolysis present in sewage was not a metabolic reaction in human liver microsome system. 26 In addition to the two identified TPs…”
Section: Identification Of Tpsmentioning
confidence: 99%